2015
DOI: 10.1002/ptr.5314
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Serotonin in the Hypoglycemic Effects Produced by Administration of the Aqueous Extract of Xylaria nigripes with Steroid-Induced Insulin-Resistant Rats

Abstract: Xylaria nigripes (XN) is a medicinal fungus with a high-economic value. The aim of this study was to explore the hypoglycemic effects and mechanisms of the XN aqueous extract in steroid-induced insulin-resistant (SIIR) rats. Significant hypoglycemic effects were observed 60 min after administration of XN aqueous extract. In normal Wistar, hypoglycemic effects were 21% (the plasma glucose level decreased from 128.6 ± 12.5 to 100.9 ± 10.7 mg/dL). In SIIR, hypoglycemic effects were 26% (the plasma glucose level d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…All tested plants exhibited antihyperglycemic properties, with inhibition factors ranging from 25.8% to 62.3%. Published antidiabetic studies of herbal drugs on in vivo OGTT models have monitored various measurements of hyperglycemia reduction (Dias et al ., ; Chen et al ., ), making difficult the comparison of efficiencies. Indeed published studies differ in animal models, duration of observation, dose of glucose, reference drug, type of plant extract; also investigated herbs probably differ in their mechanisms of action (Patel et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…All tested plants exhibited antihyperglycemic properties, with inhibition factors ranging from 25.8% to 62.3%. Published antidiabetic studies of herbal drugs on in vivo OGTT models have monitored various measurements of hyperglycemia reduction (Dias et al ., ; Chen et al ., ), making difficult the comparison of efficiencies. Indeed published studies differ in animal models, duration of observation, dose of glucose, reference drug, type of plant extract; also investigated herbs probably differ in their mechanisms of action (Patel et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that AC stimulates AMPK to enhance GLUT-4 translocation and activates the peroxisome proliferator activated receptor α (PPARα) to decrease plasma FFA levels, which may complement the insulin signaling pathway to result in a hypoglycemic effect and improvement in insulin resistance (18,20,32,34). In our previous studies, we also used the SIIR animal model to test the hypoglycemic effect of the Xylaria nigripes (Xn) fungus and the Gardenia jasminoides (GJ) plant (26,35). However, Xn was found to exert a serotonin-associated hypoglycemic effect, and PPAR activation was key to the hypoglycemic effect of GJ.…”
Section: Discussionmentioning
confidence: 99%
“…This study was performed according to previously published research methods. 17 The SIIR rats were injected intraperitoneally (i.p.) with 1 mg/kg of dexamethasone daily for 5 days.…”
Section: Animal Modelsmentioning
confidence: 99%